Cycles of Conquest : the Impact of Spain, Mexico, and the United States on Indians of the Southwest, 1533-1960 - Spicer, Edward Holland, 1906-1983 (University of Arizona Press, 1962)
After more than fifty years, Cycles of Conquest is still one of the best syntheses of more than four centuries of conquest, colonization, and resistance ever published. It explores how ten major Native groups in northern Mexico and what is now the United States responded to political incorporation, linguistic hegemony, community reorganization, religious conversion, and economic integration. Thomas E. Sheridan writes in the new foreword commissioned for this special edition that the book is "monumental in scope and magisterial in presentation." Cycles of Conquest remains a seminal work, deeply influencing how we have come to view the greater Southwest and its peoples.